Unconditional violation of the shot-noise limit in photonic quantum metrology. Issue 11 (November 2017) - Slussarenko, Sergei; Weston, Morgan; Chrzanowski, Helen; Shalm, Lynden; Verma, Varun; Nam, Sae; Pryde, Geoff
Abstract Interferometric phase measurement is widely used to precisely determine quantities such as length, speed and material properties1–3 . Without quantum correlations, the best phase sensitivity $${\boldsymbol{\Delta }}{\boldsymbol{\phi }}$$ Δ ϕ achievable usingn photons is the shot-noise limit, $${\boldsymbol{\Delta }}{\boldsymbol{\phi }}=1\, /\sqrt{{n}}$$ Δ ϕ = 1 ∕ n . Quantum-enhanced metrology promises better sensitivity, but, despite theoretical proposals stretching back decades3, 4, no measurement using photonic (that is, definite photon number) quantum states has truly surpassed the shot-noise limit. Instead, all such demonstrations, by discounting photon loss, detector inefficiency or other imperfections, have considered only a subset of the photons used. Here, we use an ultrahigh-efficiency photon source and detectors to perform unconditional entanglement-enhanced photonic interferometry. Sampling a birefringent phase shift, we demonstrate precision beyond the shot-noise limit without artificially correcting our results for loss and imperfections. Our results enable quantum-enhanced phase measurements at low photon flux and open the door to the next generation of optical quantum metrology advances. Unconditional entanglement-enhanced photonic interferometry is implemented by using a state-of-the-art photon source and detectors. Sampling a birefringent phase shift, precision beyond the shot-noise limit is demonstrated without data correction.